A New Era of Prostate Cancer Precision Medicine - Malik, Adil; Srinivasan, Srilakshmi; Batra, Jyotsna (Frontiers in Oncology, 2019)
Prostate Cancer is the second most common male cancer affecting Western society. Despite substantial advances in the exploration of Prostate Cancer biomarkers and treatment strategies, men are over diagnosed with inert Prostate Cancer, while there is also a substantial mortality from the invasive disease. Precision medicine is the management of treatment profiles across different cancers predicting therapies for individual cancer patients. Strategies including individual genomic profiling and targeting specific cancer pathways, precision medicine for Prostate Cancer has the potential to impose changes in clinical practices. Some of the recent advances in Prostate Cancer precision medicine comprise targeting gene fusions, genome editing tools, non-coding RNA biomarkers and the promise of liquid tumour profiling. In this review, we will discuss these recent scientific advances to scale up these approaches and endeavours to overcome clinical barriers for Prostate Cancer precision medicine.